A PRELIMINARY STUDY ON THE IN VITRO ANTIOXIDANT ACTIVITY OF THE STEMS OF OPUNTIA VULGARIS - Dilipkumar Pal; Sanmoy Mitra (Wolters Kluwer Medknow Publications, 2010)
The in vitro antioxidant activity of stems of Opuntia vulgaris Mill had been investigated by estimating degree of non-enzymatic haemoglobin glycosylation measured colorimetrically at 520 nm. It was found that benzene and chloroform extract of O. vulgaris had better antioxidant activity than petroleum ether, ethyl acetate, ethanol and aqueous extract. The antioxidant activity of the extracts was concentration dependent and comparable to that of D-- tocopherol (vitamin E) and ascorbic acid (vitamin C), standard antioxidant compounds used.